2016
DOI: 10.3390/publications4020018
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting Domain Loss and Epistemicide in Specialized Discourse: A Case Study on the Translation of Anglophone Metaphors to French

Abstract: Abstract:The dominance of English as the world language of publication has had a decisive impact on the dissemination of information and innovation across cultures, with a resulting tendency to a standardization of scientific conceptualization. This dominance does not only impact scientific and academic discourse, but also the whole range of professional and technical texts representative of various specialized discourses. This paper advocates engaging in the practice of dynamic translation to keep non-English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…Building on Bennett's work, Geneviève Bordet argues that French discourse is in danger of falling prey to English as well. She examines the translation of metaphors from English to French and sees translation as one potentially fruitful avenue to counter uncritical adoption of Anglo-American modes of thought and writing into French [27]. Salager-Meyer and colleagues [28], also argue that the changes they observe in Spanish medical writing from 1930 until 1995 can be attributed to Spanish scholars' engagement with English language research and the emergence of guide books and writing courses based on Anglo-American writing traditions.…”
Section: Multilingual Writing Practices and Shifting Writing Conventimentioning
confidence: 99%
“…Building on Bennett's work, Geneviève Bordet argues that French discourse is in danger of falling prey to English as well. She examines the translation of metaphors from English to French and sees translation as one potentially fruitful avenue to counter uncritical adoption of Anglo-American modes of thought and writing into French [27]. Salager-Meyer and colleagues [28], also argue that the changes they observe in Spanish medical writing from 1930 until 1995 can be attributed to Spanish scholars' engagement with English language research and the emergence of guide books and writing courses based on Anglo-American writing traditions.…”
Section: Multilingual Writing Practices and Shifting Writing Conventimentioning
confidence: 99%
“…On the basis of CMT, Merakchi and Rogers (2013) confirmed that conceptual metaphors are used to add coherence to scientific discourse, as they "evoke the knowledge space of a particular source domain or sets of source domains" (Merakchi and Rogers 2013, p. 345). Bordet (2016) also highlighted the fact that conceptual construction of scientific neologisms varies across languages, but metaphors are frequently used. In the context of specialized translation, Merakchi and Rogers (2013) found that the translation of metaphor in scientific texts is crucial in the intercultural and communicative act.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that translating specialized metaphors did pose some challenges in terms of the translation strategies available in Malay, the target language (Abdullah and Shuttleworth 2013, p. 617). In this scenario, sometimes translation processes may lead to the standardization of the underlying conceptual constructions from the source specialized domains, and to domain loss or "epistemicide" in target languages and cultures (Bordet 2016). In other words, according to Hultgren (2013, p.166), this is the failing to develop adequate scientific terminology in a national language, especially at conceptual level.…”
Section: Introductionmentioning
confidence: 99%
“…I have chosen the last of these for what follows. We have two papers from the perspectives of those supporting EAL authors at the level of individual manuscript (an author's editor [4] and a translation specialist [5], two that analyse aspects of the written texts themselves, titles [6] and abstracts [7], to gain insights of value across the community, and two that focus on how novice research authors learn their craft [8,9]. However, across these groupings additional themes are highlighted.…”
mentioning
confidence: 99%
“…To what extent do, or should, EAL authors uncritically adopt the ways of writing and constructing knowledge approved by the English-language, Western academy [4,7,8]? What processes and players are key in helping EAL authors gain acceptance for their research articles and how can their contributions be strengthened [4,5,8,9]? How can close analysis of the written text open windows onto successful practices [4,6,7]?…”
mentioning
confidence: 99%